Stability Indicating Rp-Hplc for Method Development and Validation for Simultaneous Estimation of Empagliflozin and Nateglinide in Bulk Drug - Kajol, .; Kaushik, Aditi; Sharma, Nikhil (Jordan Journal of Pharmaceutical Sciences, 2025)
A simple, accurate, and precise stability-indicating RP-HPLC method was developed and validated for the simultaneous estimation of Empagliflozin and Nateglinide in bulk drug form. Chromatographic separation was performed on a Shim-pack C-18 column (250 × 4.6 mm, 5 µm) using a mobile phase of Acetonitrile: Water (90:10, v/v) adjusted to pH 3. The UV detection wavelength was set at 216 nm, the flow rate was maintained at 1 mL/min, and the injection volume was 20 µL. The retention times for Empagliflozin and Nateglinide were found to be 2.770 and 3.682 minutes, respectively. This method was validated according to ICH Q2(R1) guidelines for linearity, accuracy, precision, limit of detection (LOD), limit of quantification (LOQ), and robustness. A linear response was observed in the concentration range of 5–25 µg/mL for Empagliflozin and 10–50 µg/mL for Nateglinide. The LOD and LOQ for Empagliflozin were found to be 14.0502 µg/mL and 42.576 µg/mL, respectively, while for Nateglinide, they were 6.5398 µg/mL and 19.8178 µg/mL. Stress studies were performed in accordance with ICH Q1A(R2) guidelines. The drugs were subjected to stress conditions including photolytic, oxidative, thermal degradation, and acid/base hydrolysis to develop a stability-indicating method. The degraded products were effectively extracted and analyzed from the sample.